Increasing Teacher Competency Through Training and Person Job Fit - Nur Hakima Akhirani Nasution; Nurul Dalimunte; Saipul Bahri Harahap; Ratna Sari Dewi; Ahmad Karim (Program Studi Manajemen Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2023)
This study aims to explore the effect of training and suitability between individual characteristics (person-job fit) on increasing teacher competence in the digital era using a qualitative approach. Amid the transformation of education by digital technology, it is important to understand how individual training and suitability for work demands play a role in developing teacher competency. This research method uses in-depth interviews with headmasters of experienced teachers from various backgrounds at Madrasah Aliyah. The results of this study reveal that training has a significant role in enriching teachers' knowledge, skills, and understanding of the use of technology in learning. Teachers who attended the training reported increasing their ability to face technological challenges and optimize teaching potential in the digital age. In addition, the suitability of individual characteristics with work tasks in the digital era also influences how teachers can more effectively integrate technology in education. This research indicates that a combination of training that is tailored to individual needs and the degree of suitability to job demands can positively affect teacher competence. in the digital age. These findings make an important contribution to the development of better professional development strategies to support teachers in coping with educational changes caused by technology.